MEMBANGUN SISTEM PELAYANAN PUBLIK YANG MEMIHAK PADA RAKYAT - Agus Dwiyanto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2002)
Public service delivery in Indonesia has failed to win the hearts of the public. Such a stance is attributed to distortions, which owe their origins to the bureaucratic structure of the organization and administration of public service provision, as well as the haphazard work practices, all of which have undermined the efficiency of public service delivery. The public, as customers of services, has been plagued by accessibility problems, persistent delays, and rampant bureaucratic corruption. The lack of responsibility and authority by those delivering public services imply that strict adherence to rigid rules and regulations takes precedence over serving the interests of the public. Public service bureaucracy in Indonesia is indeed rule rather than customer driven. Besides, customers of public services have a weak bargaining position, which precludes their raising any complaints in case the services received fall short of their expectations and a far cry from fulfilling their satisfaction. In order to revitalize the image of the civil service the government must enhance the effectiveness, efficiency, and fairness in the delivery of public services. Nonetheless, making recommendations on the quality improvement is one thing, implementing them is another, even more complex issues. A number of changes must be effected; right from the top brass down to the first-line service providers, if the much cherished more customer-driven work ethics are to be instilled.